(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the epidemiological, clinical, and laboratory characteristics, suspected triggers, and initial management of anaphylaxis at the Center for Allergy and Clinical Immunology, Bach Mai Hospital, during 2024-2025. Subjects and methods: A cross-sectional descriptive study was conducted on 325 inpatients diagnosed with anaphylaxis at the Center for Allergy and Clinical Immunology, Bach Mai Hospital, from July 1, 2024, to June 30, 2025. Data on demographic characteristics, location of symptom onset, initial responders and management, anaphylaxis severity, suspected triggers, initial clinical manifestations, and selected laboratory findings were collected and analyzed descriptively. Results: Females accounted for 66.8% of patients, with a mean age of 41.39 ± 17.42 years. Anaphylaxis most commonly occurred at home (57.5%), and the majority of patients received initial management by healthcare professionals (98.2%) at various healthcare facilities. Grade II anaphylaxis was the most frequent (55.4%). Most cases were classified as anaphylaxis with unidentified triggers (91.4%). Cutaneous and mucosal manifestations were the most common initial symptoms (83.1%), followed by respiratory symptoms (53.2%), while gastrointestinal and cardiovascular symptoms were less frequent. Elevated total IgE was found in 34.8% of patients, renal impairment in 5.5%, and elevated CRP in 24.5%. Conclusions: Anaphylaxis at Bach Mai Hospital predominantly occurred outside healthcare settings and was mainly of moderate severity. Although patients demonstrated appropriate healthcare-seeking behavior and initial management was largely guideline-adherent, the high proportion of unidentified triggers highlights limitations in exposure history assessment and patient awareness. Strengthening patient education and post-anaphylaxis follow-up is essential to improve long-term management and prevent recurrence